Hypoxia Worsens Affective Responses and Feeling of Fatigue During Prolonged Bed Rest - Stavrou, Nektarios A. M.; Debevec, Tadej; Eiken, Ola; Mekjavic, Igor B. (Frontiers in Psychology, 2018)
Previous research, although limited, suggests that both, hypoxia and bed rest influence psychological responses, by exaggerating negative psychological responses, and attenuating positive emotions. The present study investigated the effect of a 21-day prolonged exposure to bed rest and normobaric hypoxia on affective responses and fatigue. Eleven healthy participants underwent three 21-day interventions using a cross-over design: 1) normobaric hypoxic ambulatory confinement (HAMB), 2) normobaric hypoxic bed rest (HBR) and 3) normoxic bed rest (NBR). Affective and fatigue responses were investigated using the Activation Deactivation Adjective Check List, and the Multidimensional Fatigue Inventory, which were completed before (Pre), during (Day 7, Day 14, Day 21) and after (Post) the interventions. The most negative psychological profile appeared during the HBR intervention. Specifically, tiredness, tension, general and physical fatigue significantly increased on days 7, 14, and 21, as well as at Post. After the HBR intervention, general and physical fatigue remained higher compared to Pre values. Additionally, a deterioration of psychological responses was also noted during the HAMB and NBR with both, hypoxia and bed rest independently induced subjective fatigue and negative affective responses. Bed rest seems to exert a moderate effect on the sensation of fatigue, whereas exercise attenuates the negative effects of hypoxia as noted during the HAMB condition. In conclusion, our data suggest that the addition of hypoxia to bed rest-induced inactivity significantly worsens affective responses and feeling of fatigue.